Butoh : Metamorphic Dance and Global Alchemy - Fraleigh, Sondra Horton, 1939- (Book collections on Project MUSE., 2010)
"Both a refraction of the bombings of Hiroshima and Nagasaki and a protest against Western values, butoh is a form of Japanese dance theater that emerged in the aftermath of World War II. Sondra Fraleigh chronicles the growth of this provocative art form from its midcentury founding under a sign of darkness to its assimilation in the twenty-first century as a poignant performance medium with philosophical and political implications. Employing intellectual and aesthetic perspectives to reveal the origins, major figures, and international development of the dance, Fraleigh documents the range and variety of butoh artists around the world with first-hand knowledge of butoh performances from 1973 to 2008. Her definitions of butoh's morphology, alchemy, and philosophy set a theoretical framework for poetic and engaging articulations of twenty butoh performances in Japan, Europe, India, and the West. With a blend of scholarly research and direct experience, she also signifies the unfinished nature of butoh and emphasizes its capacity to effect spiritual transformation and bridge cultural differences."--Publisher.